THE INTRODUCTION OF BLOCKCHAIN TECHNOLOGIES TO OUR COUNTRY AND THEIR IMPACT ON THE ECONOMY (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the integration of blockchain technologies into our country's economic landscape and investigates their potential influence on various sectors. It outlines the basic principles of blockchain and examines its possible applications in enhancing efficiency, transparency, and security across industries such as finance, logistics, and public administration. The research highlights how blockchain could revolutionize economic processes by reducing operational costs, improving data integrity, and facilitating faster transactions. Additionally, the article discusses the obstacles that may hinder its widespread adoption, including regulatory challenges, infrastructure limitations, and the need for technical expertise. Finally, the article reflects on the long-term economic benefits of embracing blockchain, particularly in terms of fostering innovation and strengthening the country's position in the global economy.